The Benefits of Alternatives to Conventional College: Labor-Market Returns to Proprietary Schooling - Christopher Jepsen; Peter R. Mueser; Kyung-Seong Jeon (Institute for the Study of Labor (IZA), 2016)
This paper provides novel evidence on the labor-market returns to proprietary (also called for-profit) postsecondary school attendance. Specifically, we link administrative records on proprietary school attendance with quarterly earnings data for nearly 70,000 students. Because average age at school entry is 30 years of age, and because we have earnings data for five or more years prior to attendance, we estimate a person fixed-effects model to control for time-invariant differences across individuals. By five years after entry, quarterly earnings returns are around 32-35 percent for men and 25-26 percent for women. Average returns are slightly higher for associate's degree programs than certificate programs, but variation by field of study is much greater. Differences in return by gender are completely explained by differences in field of study.
Keywords: J24; I26; 330; labor-market returns; postsecondary education; proprietary schooling